The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1200/jco.1999.17.8.2461
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-CVAD Program in Burkitt's-Type Adult Acute Lymphoblastic Leukemia

Abstract: Hyper-CVAD is effective in adult B-ALL. Identification of patients with high risk for relapse and improved methods to detect residual disease may result in risk-oriented approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
165
1
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(175 citation statements)
references
References 26 publications
5
165
1
4
Order By: Relevance
“…Anderson Cancer Center, confirmed a good activity in BL patients. However, the authors observed that patients older than 60 years clearly had an inferior outcome, with a survival rate of only 17% [9]. The addition of Rituximab and the improvement in supportive care measures possibly contributed to the achievement of similar outcomes in older and younger adults [10].…”
Section: Introductionmentioning
confidence: 99%
“…Anderson Cancer Center, confirmed a good activity in BL patients. However, the authors observed that patients older than 60 years clearly had an inferior outcome, with a survival rate of only 17% [9]. The addition of Rituximab and the improvement in supportive care measures possibly contributed to the achievement of similar outcomes in older and younger adults [10].…”
Section: Introductionmentioning
confidence: 99%
“…First line chemotherapy regimens include CODOX-M plus IVAC, hyper-CVAD, or dose adjusted EPOCH [2123]. …”
Section: Discussionmentioning
confidence: 99%
“…This limits our ability to assess the risk of PH in patients with HS and ongoing hemolysis (albeit extravascular). Also from this study we cannot conclude that PH in HS does not occur at an increased frequency over the general population since idiopathic PH is extremely rare (estimated prevalence less than 0.2%) [25,26] and thus a prohibitively large number of HS patients would be required to power such a study. However, given the upper 95% confidence interval of 12% prevalence of PH for the splenectomized participants in our current study, it does not appear that splenectomy in HS confers a similar risk for PH as in thalassemia.…”
Section: Prevalence Of Pulmonary Hypertension In Hereditary Spherocytmentioning
confidence: 92%
“…However, patients at high risk with resistant disease are mostly older and comorbid, thus SCT often is not practicable. Furthermore, if patients do not respond to initial, intensive therapy, further course of disease is often fatal [25,26]. In our cohort, no patient received high dose therapy with autologous or allogeneic SCT in first remission, but autologous SCT was part of salvage-therapy in two patients.…”
mentioning
confidence: 98%
See 1 more Smart Citation